Ventilator-associated pneumonia: new principles guiding empiric antibiotic therapy. Issue 2 (April 2020) - Dominedò, Cristina; Ceccato, Adrian; Torres, Antoni
Abstract : Purpose of review: Ventilator-associated pneumonia (VAP) is a serious event in critically ill patients. We aim to review the most recent evidences about VAP, including its cause, the main differences between the American and European guidelines in the definition of risk factors for multidrug-resistant pathogens, the main principles guiding empirical antibiotic treatment, and the potential role of molecular diagnostic tests. Recent findings: The 2016 ATS/IDSA and the 2017 ERS/ESICM/ESCMID/ALAT guidelines provide different approaches for the management of VAP. Both guidelines highlight the need to use local epidemiological data for antibiotic choice; however, they identify different risk factors that can assist with decision making when local data are not available. Nevertheless, validation studies of the American guidelines suggest that empiric antibiotic therapy based on risk factors may lead to an overuse of broad-spectrum antibiotics. Rapid diagnostic tests may allow a faster identification of VAP cause, resulting in more adequate antimicrobial therapy and reduced exposition to broad-spectrum antibiotics. Summary: Clinical studies should be conducted to evaluate the benefits of implementing guidelines and new approaches such as combinations of clinical data with rapid diagnostic tests; meantime adaptations of guidelines to local settings should be carried out by a local multidisciplinary expert team.